1993
DOI: 10.1073/pnas.90.12.5509
|View full text |Cite
|
Sign up to set email alerts
|

The 110-kDa polypeptide of spinach plastid DNA-dependent RNA polymerase: single-subunit enzyme or catalytic core of multimeric enzyme complexes?

Abstract: Highly purified RNA polymerase preparations from spinach chloroplasts contain seven major polypeptides of 150, 145, 110, 102, 80, 75, and 38 kDa. I find that RNA polymerase activity can be separated under defined conditions into three different fractions by heparin-Sepharose chromatography. Immunological analysis has shown that the rEst fraction contains RNA polymerase activity associated with all seven major polypeptides, and other studies have shown that some of these polypeptides (150, 145, 80, and 38 kDa) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
96
1

Year Published

1993
1993
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(100 citation statements)
references
References 39 publications
3
96
1
Order By: Relevance
“…The identification of nuclear-encoded plastidlocalized RNA polymerase (Greenberg et al, 1984;Lerbs-Mache, 1993;Young et al, 1998) and plastidtargeted sigma factors (Tiller et al, 1991;Lahiri et al, 1999) has revealed the importance of transcriptional control in the regulation in plastid gene expression. The accumulation of both nuclear-encoded plastidlocalized RNA polymerase and plastid-localized sigma factors is normally light regulated (Chang et al, 1999;Lahiri et al, 1999) and, therefore, may be disrupted in elm1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…The identification of nuclear-encoded plastidlocalized RNA polymerase (Greenberg et al, 1984;Lerbs-Mache, 1993;Young et al, 1998) and plastidtargeted sigma factors (Tiller et al, 1991;Lahiri et al, 1999) has revealed the importance of transcriptional control in the regulation in plastid gene expression. The accumulation of both nuclear-encoded plastidlocalized RNA polymerase and plastid-localized sigma factors is normally light regulated (Chang et al, 1999;Lahiri et al, 1999) and, therefore, may be disrupted in elm1 plants.…”
Section: Discussionmentioning
confidence: 99%
“…In plastids rRNA genes are duplicated and evidence for an additional RNA-polymerase (and/or its respective cofactors) has been described, which may provide a differential tanscriptional activity (3)(4)(5). Only few of the plastid tRNA genes are located in the inverted repeat region, while most of the others appear to be cotranscribed with protein coding genes (6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…The transcriptional machinery plays an important role in the regulation of chloroplast development at different developmental stages (Mullet, 1993;Emanuel et al, 2004;Zoschke et al, 2007). Higher plant cells possess at least two types of RNA polymerases: a plastid-encoded bacterial-type RNA polymerase (PEP), which is a multisubunit eubacterium-type enzyme, and a nucleusencoded phage-type RNA polymerase (NEP) that resembles the single-subunit type shared with phage T3/T7 and mitochondrial enzymes (Hu and Bogorad, 1990;Igloi and Kö ssel, 1992;Lerbs-Mache, 1993;Pfannschmidt and Link, 1997;Liere and Maliga, 2001). The chloroplast-encoded photosynthetic genes are exclusively transcribed by PEP (class I genes).…”
mentioning
confidence: 99%